Analisis Manajemen Pendidikan Formal Gereja (Studi Katekisasi di Gereja Protestan Maluku Klasis Pulau-Pulau Obi Jemaat Wooi Kabupaten Halmahera Selatan) - Utubira, Everd Elseos Martin; Kempa, Rudolf; Lekatompessy, Jantje Eduard (LP. Ma'arif Janggan Magetan, 2023)
This research is a type of qualitative research with a phenomenological paradigm that aims to reveal facts about the appearance that occurs in management in catechization education as well as inhibiting and supporting factors. The results showed that the planning of catechization education in GPM Wooi Church started from the mechanism for accepting students, the cost of sidi letters, rules and educator incentives. In organizing there is a division of tasks, delegation of authority and teaching schedules. Meanwhile, in the implementation activities, it was found that the implementation of catechization education learning activities in one week was two meetings, namely Tuesday and Friday and there were two semesters for one academic year, each semester of which learning activities required six months. Evaluation in catechization education includes evaluation of learning outcomes and evaluation of educator performance. The mechanism for evaluating learning outcomes is carried out by techniques of written tests, oral tests and faith tests and the end of this education is confirmation to become a new member of the Moluccan Protestant Church.